On Some New Inequalities of Hermite–Hadamard Type for Functions Whose Derivatives are $s$-Convex in the Second Sense in the Absolute Value - Latif, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
Several new inequalities of the Hermite–Hadamard type are established for functions whose derivatives are s-convex in the second sense in the absolute value. Some applications to special means of positive real numbers are also presented.